The future of green building: The role of VR and artificial intelligence in improving BIM efficiency - Borisova Tatiana; Molchanova Yulia; Ermakova Evgenia (E3S Web of Conferences)
Building information modeling (BIM), virtual reality (VR) and artificial intelligence (AI) technologies are becoming key tools in the construction industry, improving design, construction and management processes. They ensure high coordination and accuracy, accelerate error detection and improve the quality of execution. The article examines successful examples of the use of these technologies and their impact on all stages of the construction life cycle, including planning, operation and renovation. The integration of BIM, VR and AI can significantly increase efficiency and reduce the need for human resources.